Bargaining for Contract Academic Staff at English Canadian Universities. Issue 3 (September 2015) - Hughes, Jula; Bell, David; Newfield, Marcia; Berry, Joe; Kroik, Polina
<x xml:space="preserve">Abstract</x> Successful unionization of, and conclusion of collective agreements for, contract academic staff in English Canada challenges the received wisdom that the Wagner Act model is an insurmountable obstacle to the unionization of contingent labor. It provides an example that might prove instructive for other contingent workers. This article describes the process of unionization of contract academic staff in English Canada and seeks to explain its relative success. The exceptional situation of contract academic staff as nonunionized workers in an otherwise unionized environment, access to the expertise and resources of large, national unions or associations and a sophisticated national strategy were contributing factors to successful unionization. The article also considers the degree to which contract academic staff collective agreements fulfill the promise of unionization. We analyze sample collective agreements, noting the variety and strength of various contractual models. We conclude by suggesting that contract academic staff have benefitted considerably from unionization. Despite these successes, the experience of contract academic staff supports critiques of the Wagner Act model as applied to contingent labor.